2015
DOI: 10.1186/s12879-015-1145-z
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of the incidence, clinical characteristics, identification, and antimicrobial susceptibility of bacteremic isolates of Acinetobacter ursingii

Abstract: BackgroundAcinetobacter ursingii bacteremia is rarely reported. We investigated the incidence and clinical features of A. ursingii bacteremia, performance of the identification system, and antimicrobial susceptibility of the isolates. Acinetobacter ursingii bacteremia patients were compared with A. baumannii bacteremia patients.MethodsIn this 9-year retrospective study, A. ursingii was identified using 16S rRNA and 16S–23S rRNA internal transcribed spacer sequence analysis. The performances of the Vitek 2, Pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Furthermore, the clinical strains of non-baumannii Acinetobacter species were substantially less lethal during infection in wax moth larvae of Galleria. Similarly, in a case-control study, patients infected with A. ursingii had much lower 28-day mortality than those infected with A. baumannii (6% versus 37%) even though multidrug resistance and inadequate initial therapy were as likely to occur in patients infected with either species (10).…”
Section: Acinetobacter Virulence Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the clinical strains of non-baumannii Acinetobacter species were substantially less lethal during infection in wax moth larvae of Galleria. Similarly, in a case-control study, patients infected with A. ursingii had much lower 28-day mortality than those infected with A. baumannii (6% versus 37%) even though multidrug resistance and inadequate initial therapy were as likely to occur in patients infected with either species (10).…”
Section: Acinetobacter Virulence Factorsmentioning
confidence: 99%
“…The most common species to cause infections is A. baumannii, followed by A. calcoaceticus and A. lwoffii (4). Additional species, including A. haemolyticus, A. johnsonii, A. junii, A. nosocomialis, A. pittii, A. schindleri, and A. ursingii, have occasionally been reported as pathogens (5)(6)(7)(8)(9)(10)(11). A. seifertii is an emerging pathogen in Asia; it is genetically closely related to and may be misidentified as A. baumannii (12)(13)(14).…”
mentioning
confidence: 99%
“…Although there has been reports of deaths and morbidity associated with neonatal outbreaks due to A. ursingii ,9 a retrospective study by Chiu et al concluded that patients with A. ursingii bacteraemia usually have overall lower disease severity and mortality rates than patients with A. baumannii bacteraemia,8 which might explain the good outcome seen in our case.…”
Section: Discussionmentioning
confidence: 52%
“…Acinetobacter infections in neonatal intensive care units are described in literature, but the subspecies ursingii is rarely isolated 2. In a study by Chiu et al , of a sample of 616 patients with Acinetobacter species bacteraemia, 3.1% were identified as A. ursingii 8. It has lower pathogenic potential than A. baumannii , but it has also been recognised as an opportunistic agent in hospitalised and immunocompromised patients 2…”
Section: Discussionmentioning
confidence: 99%
“…Bloodstream infection due to Acinetobacter baumannii is characteristically a nosocomial infection with a fatality rate of up to 37% (1). Suspicion of bloodstream infection warrants immediate blood tests, and if bloodstream infection is confirmed, pathogen-based treatment should be initiated immediately.…”
Section: Introductionmentioning
confidence: 99%